2015
DOI: 10.1016/j.npep.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatography-electrospray linear ion trap mass spectrometry analysis of targeted neuropeptides in Tac1−/− mouse spinal cords reveals significant lower concentration of opioid peptides

Abstract: Tachykinin and opioid peptides play a central role in pain transmission, modulation and inhibition. The treatment of pain is very important in medicine and many studies using NK1 receptor antagonists failed to show significant analgesic effects in humans. Recent investigations suggest that both pronociceptive tachykinins and the analgesic opioid systems are important for normal pain sensation. The analysis of opioid peptides in Tac1 -/-spinal cord tissues offers a great opportunity to verify the influence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…As a result of mutations (e.g., disease-related, radiation, chemicals, and pathogens) or genetic manipulations, losses of phosphorylation sites might disrupt protein binding and deregulate signal transduction, including pain signaling pathways. As we have shown previously, the absence of SP, a proteolytic product of TAC1, has an impact on the abundance of opioid peptides and therefore on the endogenous pain-relieving mechanisms (Saidi and Beaudry, 2015). Thus, we wanted to verify whether Tac1 -/- mice show defective pain modulatory pathways by specifically profiling specific protein kinases.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…As a result of mutations (e.g., disease-related, radiation, chemicals, and pathogens) or genetic manipulations, losses of phosphorylation sites might disrupt protein binding and deregulate signal transduction, including pain signaling pathways. As we have shown previously, the absence of SP, a proteolytic product of TAC1, has an impact on the abundance of opioid peptides and therefore on the endogenous pain-relieving mechanisms (Saidi and Beaudry, 2015). Thus, we wanted to verify whether Tac1 -/- mice show defective pain modulatory pathways by specifically profiling specific protein kinases.…”
Section: Resultsmentioning
confidence: 86%
“…However, Tac1 -/- mice presented a behavioral phenotype similar to that of wild-type mice following light or nonpainful stimuli (Zimmer, 1998). Our previous study revealed that the absence of SP in Tac1 -/- mice hindered the release of endogenous opioid peptides, thereby negatively impacting endogenous pain-relieving mechanisms (Saidi and Beaudry, 2015). Furthermore, we have demonstrated that TAC1 is processed by proprotein convertase 1/3 (PC1/3) and proprotein convertase 2 (PC2), leading to a precursor of SP (Saidi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This experimental design requires substantial knowledge about the presence of NPs in the sample and details about NP structural characteristics. For targeted NP quantitation, multiple-reaction monitoring (MRM) is perhaps one of the most commonly employed techniques, offering high precision, high sensitivity, and high throughput (38,39). It is also important to define two types of quantitative measurements in the field of MS: A quantitative measurement provides relative quantitation between samples, whereas absolute quantitation provides an absolute amount (or concentration) of peptide.…”
Section: Targeted Mass Spectrometry Quantitationmentioning
confidence: 99%